Role of dentifrice in plaque removal: A clinical trial - Jayakumar A; Padmini H; Haritha A; Reddy Krishnanjaneya (Wolters Kluwer Medknow Publications, 2010)
Background: The precise role of dentifrice in plaque removal has been debatable. While a considerable volume of literature attributes several beneficial properties and glorifies the role of dentifrice, a small body of researchers questions its efficacy. Lingering doubts are emerging about the plaque removal efficacy of toothpastes and probably a time has come to reassess its role in plaque removal. Aim: The present study is used to evaluate the plaque removal efficacy of dentifrice alone during the manual brushing of teeth. Materials and Methods: In a double blinded 2 Χ 2 crossover study design, 42 subjects had brushed randomly with or without dentifrice under supervision, with a standard dentifrice and toothbrush, after 48 hours of plaque accumulation, for two minutes. Results: Plaque reduction with dentifrice was 57.35% and without dentifrice was 66.19%. This 9% difference was statistically significant ( P ≤ 0.001). Conclusion: Dentifrice use does not enhance plaque removal when used in conjunction with a toothbrush, and instead, may marginally lessen the brushing effect. The role of a toothbrush appears to be more crucial in the maintenance of oral hygiene.